OOCYTES OF HOLOTHURIA LEUCOSPILOTA (ECHINODERMATA: HOLOTHUROIDEA): AN ULTRA STRUCTURAL STUDY - Purwati, Pradina (Marine Research in Indonesia, 2009)
Ovaries of Holothuria leucospilota consist of simple tubules, within which oocytes grew and reached maturity. The oocytes development started at the tubule lining and as the development proceeded, the oocytes increased in size and moved to the tubule lumen. An ultra-section-method was applied to describe ultrastructural changes in the oocytes during their development, leading to the knowledge on gametogenesis of sea encumber H.leucospiota. Primary previtellogenic oocytes embedded in tubule lining was the earliest stage, which were characterized by the presence of nuage. Prior to yolk formation, clusters of mitochondria appeared in the ooplasm. This may indicate the need for energy to produce yolk substance. When yolk bodies were common in vitellogenic oocytes, nuage became invisible and mitochondria were no longer in groups. As development progressed, abundant microvilli appeared on the surface of vitellogenic oocytes, but less common on postvitellogenic oocytes when maximum growth had been attained. This structure was suggested to facilitate size increase and functional efficiency of oocyte surface.